An open-label, pharmacokinetic study of lenalidomide and dexamethasone therapy in previously untreated multiple myeloma (MM) patients with various degrees of renal impairment – validation of official dosing guidelines. Issue 8 (2nd July 2020) - Chen, Christine I.; Cao, Yanshuo; Trudel, Suzanne; Reece, Donna E.; Kukreti, Vishal; Tiedemann, Rodger; Prica, Anca; Paul, Harminder; Le, Lisa W.; Levina, Olga; Kakar, Sumeet; Lau, Anthea; et al.
Abstract: Lenalidomide is a backbone agent in the treatment of multiple myeloma, but dose adjustment is required for those with renal impairment (RI). We evaluated the pharmacokinetics (PK) and safety of lenalidomide and dexamethasone as frontline pre-transplant induction, with doses adjusted at start of each cycle based on creatinine clearance, as per the official dosing guidelines. After 4 cycles, PK studies showed that patients with moderate RI (30 ≤ CrCl < 60 mL/min) receiving 10 mg dosing may be under-dosed and those with severe RI (CrCl <30ml/min) appeared appropriately dosed initially, but sustained significant decreases in maximum serum concentration (Cmax) after repeated dosing, due to rapid clinical improvement and enhanced drug clearance. PK drug monitoring during cycle 1 may facilitate appropriate and timely dose adjustments. Adverse events rates did not vary based on severity of RI. No patient discontinued lenalidomide for toxicity. This supports the feasibility and safety of frontline lenalidomide in transplant-eligible patients with RI.